2020
DOI: 10.1016/j.actbio.2020.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Orally administrated chitosan microspheres bind Helicobacter pylori and decrease gastric infection in mice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…Many factors were considered as the causative of a different outcome, such as animal model strain, H . pylori strain, and inoculation period 14,15,22,40,41,43,62‐75 . The relevance of inoculation duration in the pathological result of H .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors were considered as the causative of a different outcome, such as animal model strain, H . pylori strain, and inoculation period 14,15,22,40,41,43,62‐75 . The relevance of inoculation duration in the pathological result of H .…”
Section: Resultsmentioning
confidence: 99%
“…Many factors were considered as the causative of a different outcome, such as animal model strain, H. pylori strain, and inoculation period. 14,15,22,40,41,43,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] The relevance of inoculation duration in the pathological result of H. pylori infection was demonstrated in research by Bazin et al 15 Using the C57BL/6 mouse strain and the SS1 H. pylori strain, the early infection caused inflammation and caused hyperplasia after 3 months, but the inoculation caused intestinal metaplasia after 18 months. During the inoculation period, the consequence becomes increasingly severe.…”
Section: Figure Adapted Frommentioning
confidence: 99%
“…32 Helicobacter is a well-known human pathogen that causes gastritis and gastric cancer. 33 Fortunately, MFGs (especially human MFGs) effectively inhibited the crosslinking of module III by these pathogens, thereby reducing the risk of disease.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 123 , 125 Moreover, their results showed that chitosan microspheres can eradicate H. pylori through adhesion and are subsequently eliminated from the gastrointestinal tract. 126 Based on this idea, Adebisi et al also designed a clarithromycin-loaded chitosan hybrid microsphere and found that chitosan causes a significantly high adhesion of the microsphere to H. pylori . 124 …”
Section: Nanoparticlesmentioning
confidence: 99%